Development of a novel UHPLC-MS/MS method for the determination of ochratoxin A in tea - Cina, Mariel (2021)
The mycotoxin Ochratoxin A (OTA) is responsible for producing many effects on human and animal health. In this work, the evaluation of the presence of OTA in tea beverage samples consisted of extraction and preconcentration through the solidification of a floating organic drop (DLLME-SFO) combined with an additional octadecyl silane clean-up step. The obtained extract was analyzed by UHPLC-MS/MS. Interferences from the matrix were effectively reduced and, consequently, recovery increased from 43.18% ± 4.1%?96.02% ± 2.54%. The validation assays were carried out by external calibration and spiked samples, with satisfactory recoveries. An adequate dynamic calibration range was obtained over a concentration interval between 0.5 and 70 μg mL−1 OTA. Capabilities of detection and quantification were 0.5 and 1.4 μg mL−1. The obtained Green Certificate was compared with other techniques to establish the greenness profile of the procedure. Quantification of ochratoxin A levels in tea samples was performed.